A prototype of a digital salon management system - Odipe, Rosemary Abimbola (2025)
This thesis explores the development of a digital salon management system, designed to address the inefficiencies common in traditional salon operations. Using Yuri Lagos as a case example, the project aims to improve how customers book appointments, get matched with stylists, and engage with salon services. The work follows a design thinking approach, starting from user research and ending with a high-fidelity prototype. The prototype, created using Figma, includes key features such as appointment booking, stylist availability tracking, and a virtual hairstyle try-on experience. While the full system was not implemented, technologies like React, Firebase, and AI models were proposed for future development. User testing was conducted to evaluate the design, and feedback showed strong interest and acceptance, especially around ease of use and the potential for personalization. Suggestions like appointment reminders and loyalty programs also emerged. Overall, the project demonstrates how a well-designed digital platform can enhance the salon experience, improve efficiency, and better meet client expectations in today’s beauty industry.